Disease Tolerance in Toxoplasma Infection - Melchor, Stephanie J.; Ewald, Sarah E. (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is a successful protozoan parasite that cycles between definitive felid hosts and a broad range of intermediate hosts, including rodents and humans. Within intermediate hosts, this obligate intracellular parasite invades the small intestine, inducing an inflammatory response. Toxoplasma infects infiltrating immune cells, using them to spread systemically and reach tissues amenable to chronic infection. An intact immune system is necessary to control life-long chronic infection. Chronic infection is characterized by formation of parasite cysts, which are necessary for survival through the gastrointestinal tract of the next host. Thus, Toxoplasma must evade sterilizing immunity, but still rely on the host's immune response for survival and transmission. To do this, Toxoplasma exploits a central cost-benefit tradeoff in immunity: the need to escalate inflammation for pathogen clearance vs. the need to limit inflammation-induced bystander damage. What are the consequences of sustained inflammation on host biology? Many studies have focused on aspects of the immune response that directly target Toxoplasma growth and survival, commonly referred to as “resistance mechanisms.” However, it is becoming clear that a parallel arm of the immune response has evolved to mitigate damage caused by the parasite directly (for example, egress-induced cell death) or bystander damage due to the inflammatory response (for example, reactive nitrogen species, degranulation). These so-called “disease tolerance” mechanisms promote tissue function and host survival without directly targeting the pathogen. Here we review changes to host metabolism, tissue structure, and immune function that point to disease tolerance mechanisms during Toxoplasma infection. We explore the impact tolerance programs have on the health of the host and parasite biology.